A Call for the Conceptual Integration of Opportunity Structures Within School Safety Research. Issue 2 (3rd July 2021) - Astor, Ron Avi; Noguera, Pedro; Fergus, Edward; Gadsden, Vivian; Benbenishty, Rami
Abstract: Few studies explicitly examine how opportunity structures impact school safety, school climate, or bullying. This article applies school-centered ecological theory as a heuristic conceptual framework that links opportunity structures and school safety. Historically, opportunity structures identified how institutional characteristics such as labor conditions, combined with factors such as geographic location, gender, race, religion, nationality, ethnicity, and family background, influence the opportunities open to individuals and shape patterns of entering the labor market. In education, the concept has been used when describing systemic racism in educational inequality. Examples are drawn from several bodies of research that have strong implications for future study of these issues. These areas include research on communities and families, creating positive school cultures and climates, and different types of educator bias that restrict opportunities and result in less safe environments. The authors suggest new research that combines school safety, opportunity, and social justice-oriented school reform. Impact Statement Opportunity gaps based on social injustice often overlap with school safety concerns. Yet most school safety studies and interventions focus on individuals or interpersonal relationships and not on structurally changing opportunity or safety gaps. This article calls for new research, intervention, and policy approaches that jointly address opportunity and school safety gaps. Examples include research on (a) school-community opportunity and safety gaps, (b) low resourced schools' opportunity and safety gaps, and (c) racially biased classroom interactions that decrease opportunity and increase safety gaps.